Conservative Management of Os Navicularis in a Boxer: A Case Report - Geetika R. Jadon; Jayant Rastogi; Roshan Adkitte; Manoj Yadav; Chandra Sekara Guru (Medical Journal of Dr. D.Y. Patil Vidyapeeth)
Os navicularis is an accessory navicular bone which is seen in about 15-20% of the normal population. It requires treatment if it becomes symptomatic, more so in case of highly active athletes. A 15-year-old male boxer with complaints of pain and discomfort in the right ankle off and on. Tenderness at the N spot (proximal dorsal portion of the navicular bone), manual muscle tests showed pain in plantar flexion, eversion, and reduced power in ankle movements. Diagnosis, often delayed, relies on plain radiographs, with further imaging for type confirmation. Treatment was primarily conservative; surgery is a secondary option. Here, we report successful 12-month conservative management of a young boxer’s Os navicularis, using structured rehabilitation for full recovery. Os navicularis condition is common in youth. During management, little attention is given to vital structured rehabilitation. We advise referring patients for supervised, customized strengthening programs by experts.